2022
DOI: 10.5603/rpor.a2022.0049
|View full text |Cite
|
Sign up to set email alerts
|

In vitro radiosensitization by eribulin in human cancer cell lines

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Furthermore, while our results suggest that olaparib enhanced eribulin-induced cell cycle arrest in all cells, there is a heterogeneous response to the combination of both drugs on apoptosis. This agrees with the reported effect of eribulin on cell cycle progression and heterogenous induction of programmed cell death [39,40].…”
Section: )supporting
confidence: 93%
“…Furthermore, while our results suggest that olaparib enhanced eribulin-induced cell cycle arrest in all cells, there is a heterogeneous response to the combination of both drugs on apoptosis. This agrees with the reported effect of eribulin on cell cycle progression and heterogenous induction of programmed cell death [39,40].…”
Section: )supporting
confidence: 93%
“…They reported that apoptotic cells even after 6 Gy radiation were not increased significantly. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%